FINANCIAL LOSSES FROM CORRUPT PRACTICES: COMPARATIVE ANALYSIS OF THE REPUBLIC OF INDONESIA AND THE KINGDOM OF SAUDI ARABIA - Gufran M.I.P.; Madjid A.; Noerdajasakti S.; Anshari T. (Russian Journal of Agricultural and Socio-Economic Sciences, 2024)
For almost twenty-five years, pure economic loss claims have been the focus of intensive tort law debate, with varying views on whether the court should grant or reject them. There is only financial or economic loss when a third party suffers pure economic harm as a result of carelessness. This article will provide fascinating instances of Indonesia's utter financial devastation.. This essay will also address a number of disagreements regarding the concept and relevance of pure economic loss. The foresee ability principle, absolute vs. relative rights, the floodgates, the floodgates in conjecture, and geography are frequently the topics of these disagreements. On the other hand, those who agree to pure economic loss claim that their loss will be lawfully limited or reimbursed within the scope of contract law. After that, a legal scholar's perspective on pure economic loss will be presented, along with an approach to law and economics. In conclusion, Indonesian legal experts—especially lawmakers and judges—need to recognize the possibility of pure economic loss and determine the limits of what the legal system in the nation will accept as pure economic loss. This comparative normative legal study compares the recovery of state losses caused by corruption in Saudi Arabia and Indonesia. This study provides confirmation for that.The current legal framework in Indonesia for the gathering and seizure of assets connected to corruption has to be revised in order to recover monetary losses to the state. Secondly, there is a need to reinforce the existing mechanisms in place to combat corruption in law enforcement, specifically the procedure for recouping state losses. Indonesia's corrupt asset recovery system is less successful than Saudi Arabia's, where corruptors may lose up to 70% of their money that is taken by the government. Third, while confiscating corrupt assets in Indonesia, the notion of unexplained riches must be used. This method permits the seizure of property owned by individuals whose worth greatly above their known income and who are unable to demonstrate through reverse engineering that they obtained the property lawfully.